Identification and characterization of immune-related microRNAs in hybrid snakehead(Channa maculata♀ × Channa argus♂)after treated by Echinacea purpurea (Linn.) Moench. Issue 135 (April 2023) - Tang, Xuelian; Fu, Jinghua; Yao, Ya; Xu, Minjun
Abstract: Echinacea purpurea (Linn.) Moench (EP) is a globally popular herbal medicine, which showed effects on growth promotion, antioxidant and immunomodulatory activities in fish culture world widely. However, there are few studies about the effects on miRNAs by EP in fish. The hybrid snakehead fish ( Channa maculate ♀ ×  Channa argus ♂) was new important economic specie of freshwater aquaculture in China with high market value and demand while there were only a few reports about its miRNAs. To overview immune-related miRNAs of the hybrid snakehead fish and to further understand the immune regulating mechanism of EP, we herein constructed and analyzed three small RNA libraries of immune tissues including liver, spleen and head kidney of the fish with or without EP treatment via Illumina high-throughput sequencing technology. Results showed that EP can affect the immune activities of fish by the miRNA-regulated ways. Totally, 67 (47 up and 20 down) miRNAs in liver, 138 (55 up and 83 down) miRNAs in spleen, and 251 (15 up and 236 down) miRNAs in spleen were detected, as well as 30, 60, 139 kinds of immune-related miRNAs belonging to 22, 35 and 66 families of the three tissues respectively. The expressions of 8 immune-related miRNA family members were found in all the three tissues, including miR-10, miR-133, miR-22 and etc. Some miRNAs have been identified involved in the innate and adaptive immune responses, such as the miR-125, miR-138, and miR-181 family. Ten miRNA families with antioxidant target genes were also discovered, including miR-125, miR-1306, and miR-138, etc. Results from Gene Ontology (GO) and KEGG pathway analysis further confirmed there are a majority immune response targets of the miRNAs involved in the EP treatment process. Our study deepened understanding roles of miRNAs in fish immune system and provides new ideas for the study of immune mechanism of EP. Highlights: The miRNAs were investigated in hybrid snakehead fish treated by EP. Results indicated EP regulated the miRNAs expressions in hybrid snakehead fish. Eight immune-related miRNA family members were confirmed in the fish. Ten miRNA families with antioxidant target genes were also detected in the fish. It is the first time to discover the regulation roles of EP on miRNAs in fish.